2012
DOI: 10.1080/13691058.2011.630756
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk among drug-using men who have sex with men, men selling sex, and transgender individuals in Vietnam

Abstract: Knowledge about drug use and its association with HIV risk among men who have sex with men is limited. Although the HIV epidemic among this population in Vietnam is increasingly acknowledged, understanding the impact of drug use on the spread of HIV is largely lacking. Using qualitative data from in-depth interviews and focus group discussions with 93 drug users, 15 non-drug users and 9 community stakeholders, this analysis explores emerging patterns of drug use and risk factors for engaging in risk behaviours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…For example, surveillance reports show that the prevalence of HIV among MSM in Hanoi is currently estimated to be 19.8% (an increase from 11.0% in 2006; Ministry of Health, 2010, 2011). Similar increases were observed among MSM in Ho Chi Minh City (HCMC), currently estimated at 14.3% (an increase from 6.2% in 2006) and there is general agreement that sharp increases in the use of synthetic drugs (notably ATS) have contributed to sexual transmission among MSM (Vu et al, 2012). …”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…For example, surveillance reports show that the prevalence of HIV among MSM in Hanoi is currently estimated to be 19.8% (an increase from 11.0% in 2006; Ministry of Health, 2010, 2011). Similar increases were observed among MSM in Ho Chi Minh City (HCMC), currently estimated at 14.3% (an increase from 6.2% in 2006) and there is general agreement that sharp increases in the use of synthetic drugs (notably ATS) have contributed to sexual transmission among MSM (Vu et al, 2012). …”
Section: Introductionmentioning
confidence: 70%
“…While most of these synthetic substances are not injected, and hence do not confer the same risks for injection-mediated HIV transmission, there is nevertheless substantive concern regarding the potential for these substances to contribute to sexual risk. Indeed, STI/HIV rates have increased sharply concomitant with rapid increases in the availability and use of synthetic drugs, particularly in younger age cohorts (Vu et al, 2012, Clatts et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug use has a strong link with male-to-male commercial sex. 22,23 As shown in our study, MSM who self-identified as heterosexual males may play an important role in acting as a bridge for HIV/STIs from high-risk populations to the general population because of their prevalent bisexual behaviors and low condom usage in both male and female partnerships. Similar to findings among Cambodian MSM, 24 our results strongly indicated that having unprotected sex with an FSW significantly increased the likelihood of HIV infection among Vietnamese MSM.…”
Section: Discussionmentioning
confidence: 91%
“…Among the factors contributing to the growth of HIV infection rates in MSM populations, drug abuse has emerged as a significant contributing factor, both in relation to sexual risk as well as in the context of injection mediated transmission risk (Go et al, 2011, Quan et al, 2010, Thanh et al, 2009, Clatts et al, 2007, Vu et al, 2012, Clatts et al, 2010). Male sex workers (MSW), notably a group that is represented within the YMSM population as a whole, are of particular concern in relation to risk for HIV infection because they may have high risk behavioral interactions with multiple populations with high background HIV seroprevalence, including adult MSM (clients that purchase sex as well as non-client partners), injection drug users (IDUs) and female sex workers (Baral et al, 2015).…”
Section: Introductionmentioning
confidence: 99%